2022
DOI: 10.1037/mot0000258
|View full text |Cite
|
Sign up to set email alerts
|

Poor sleep quality is significantly associated with effort but not temporal discounting of monetary rewards.

Abstract: Experimental sleep deprivation has been shown to differentially affect behavioral indices of effort and temporal discounting, 2 domains of reward processing often observed to be impaired in depression. Experimental sleep deprivation is phenomenologically different from sleep deprivation in everyday life (e.g., poor quality sleep or habitual short sleep duration). Thus, experimental findings may not explain how sleep disturbance impacts reward processing in everyday life. The present study examined associations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 59 publications
(47 reference statements)
0
8
0
Order By: Relevance
“…In contrast to DD, the associations of sleep quality and perceived stress with ED were marginal in the present study. This observation contrasts with findings demonstrating that poorer sleep quality and reduced sleep duration are associated with less preference for high effort and high rewards, but not DD among healthy young adults [36,49]. Further, while the literature on the impact of stress on ED in humans is scant, in rats, stress exposure is related to decreases in preference for high effort, high-rewards [51].…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…In contrast to DD, the associations of sleep quality and perceived stress with ED were marginal in the present study. This observation contrasts with findings demonstrating that poorer sleep quality and reduced sleep duration are associated with less preference for high effort and high rewards, but not DD among healthy young adults [36,49]. Further, while the literature on the impact of stress on ED in humans is scant, in rats, stress exposure is related to decreases in preference for high effort, high-rewards [51].…”
Section: Discussionmentioning
confidence: 60%
“…The relevance of ED to addiction recovery has been hypothesized, noting overcoming addiction, remaining abstinent, and pursuing non-drug activities is effortful [9]. Furthermore, studies in healthy adults and animals have shown that sleep deprivation, fatigue, and acute stressors increased ED rates [36,[49][50][51][52].…”
Section: Introductionmentioning
confidence: 99%
“…higher p-factor) could have yielded even stronger results. The null results in the “cognition” domain of the PhAB-Brief documented here may be attributable to our use of a temporal discounting task instead of an effort-based discounting task [ 16 ]; future work should explore differences in discounting task designs and seek to understand how insomnia may differentially impact each of these impulsivity measures. Participant responses on some items may have been impacted by recall and social desirability biases [ 53 ] and the relatively small sample size limits the generalizability of our findings.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, these disruptions can manifest as differences in incentive-related decision-making that can be measured using validated metrics [ 9 , 13 , 15 17 ]. Moreover, sleep quality can impact how individuals choose to respond (e.g., to avoid) exertion of effort [ 16 ], which could be a mechanism for poorer performance on a variety of tasks. Sleep quality may thus influence a set of neurofunctional domains that are believed to predict substance use treatment outcomes [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…On a behavioural level, sleep deprivation, poor sleep quality, and insomnia were linked to low motivation in effort-based decision-making [52][53][54] and evening brightlight exposure enhanced effort willingness, possibly by enhancing dopamine through melatonin suppression 55 . Early chronotype predicted treatment effect on motivational behaviour in a sample of depressed subjects with comorbid insomnia 56 .…”
Section: Introductionmentioning
confidence: 99%